AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK DAUN KEMANGI (Ocymum x africanum L.) DENGAN DAUN PEPAYA (Carica papaya L.) TERHADAP Staphylococcus aureus - Samsuar Samsuar; Yuli Wahyu Tri Mulyani; Ayu Mirda Sari (JFL : Jurnal Farmasi Lampung, 2023)
Abstract Infectious diseases are one of the diseases that have suffered by many Indonesian people for a long time. S. aureus bacteria is the cause of pyogenic infections. Basil plants (Ocymum x africanum L.) and papaya plants (Carica papaya L.) can be used as antibacterial. This study aims to determine the antibacterial activity of the combination of basil and papaya leaf extracts against S. aureus bacteria. Using the Experimental Method with a combination of extract concentrations, namely K1 (0+100%), K2 (20%+80%), K3 (40%+60%), K4 (50%+50%), K5 (60%+40% ), K6 (80%+20%), K7 (100%+0%), K(-) aquadest, K(+) Oxfloxacin, followed by a test for S. aureus bacteria using the well method. The test results were analyzed using One Way Annova. with sig value (0.000) < p-value (0.05) followed by Tukey's further test which showed the combination of concentrations showed significant differences between the test groups. From this explanation, it can be concluded that the combination of basil leaf extract and papaya leaf extract can increase the inhibition zone, the largest inhibition zone is in K4 (50% basil leaf extract + 50% papaya leaf extract) the inhibitory response that appears 19.69 mm belongs to the strong category. inhibit the growth of S. aureus bacteria. Keywords: Antibacterial, basil leaf, papaya leaf, Staphylococcus aureus.